Modelling and simulation of complex cellular models using Cell-DEVS. (February 2016) - Wainer, Gabriel; Fernández, Joaquín
Cellular automata are discrete dynamical systems that provide a mathematical framework for modelling, studying and predicting the behaviour and response of systems across many different disciplines and domains, ranging from physical and biological to computational and social models. Cell-DEVS is a formalism that provides a discrete event approach to define cellular models with timing delay constructions and using simple definition of complex timing. It has been shown that the application of the Cell-DEVS paradigm produces a significant reduction in the development times of cell-shaped models and a wide variety of complex models has been developed using this approach. In this work we present the definition of complex cellular automata models using the Cell-DEVS paradigm, we use the CD++ tool to obtain executable models and study their behaviour through computer simulation.